Regional climate response to land cover change in tropical West Africa: a numerical sensitivity experiment with ESA land cover data and advanced WRF-Hydro - Mortey, Eric Mensah; Arnault, Joël; Inoussa, Maman Maarouhi; Madougou, Saïdou; Annor, Thompson; Laux, Patrick; Dieng, Mame Diarra Bousso; Kunstmann, Harald (Frontiers in Water, 2024)
The response of regional climate models (RCMs) to different input land cover information is complex and uncertain. Several studies by the regional climate modeling community have investigated the potential of land cover data to help understand land-atmosphere interactions at regional and local scales. This study investigates the regional climate response to introducing European Space Agency (ESA) land cover (LC) data into WRF-Hydro. In addition, this study assesses the potential impacts of afforestation and deforestation strategies on regional water and energy fluxes. An extended version of WRF-Hydro that accounts for a two-way river-land water flow to reduce unrealistic peaks in simulated discharge was employed. The two-way river-land flow setup yielded a better NSE and KGE of 0.47 and 0.69, respectively, over the Kulpawn basin compared to the default setup values of −0.34 and 0.2. Two land use/land cover change effects were deduced from synthetic numerical sensitivity experiments mimicking afforestation by closed shrubland expansion and deforestation by cropland expansion. The afforestation experiment yielded approximately 6% more precipitation, 3% more evapotranspiration, 27% more surface runoff, and 16% more underground runoff, while the deforestation by cropland expansion yielded −5% less precipitation, −3% less evapotranspiration, −3% less surface runoff, and − 9% less underground runoff over the Sissili-Kulpawn Basin (SKB). This result suggests that afforestation (deforestation) could increase the flood (drought) risk. Our synthetic numerical experiment mimics the regional water and energy budgets well and can help climate services and decision-makers by quantifying regional climate response to potential land cover changes.